THE RELATIONSHIP BETWEEN OCCUPATIONAL STRESS AND JOB PERFORMANCE AMONG EMPLOYEES OF ACCOUNTING FIRMS: A MEDIATING ROLE OF JOB SATISFACTION - Nisha (The journal of contemporary issues in business and government, 2022)
Employees are one of the most important parts of any organisation. An organisation’s performance is based on the performance of its employees. Special attention should be given to identify the factors which affect their performance. Occupational stress is one of the main problems of the organisations now-a-days. Occupational stress not only affects one's personal life but also their professional life. It leads to a decrease in job satisfaction reduces job commitment to the organization and may subsequently result in increased intention to quit. This paper examines the impact of job stress on employees of public accounting firms job performance. The responses of 354 employees of public accounting firms to a survey questionnaire were analysed using structural equation modelling. The structural model comprises measures of job stress, job satisfaction, job commitment and job performance. The results indicate that job stress has a direct and negative impact on levels of job commitment and job satisfaction of the employees of public accounting firms. The cognitive role of job stress has a direct and negative impact on job performance. It was also found that there is an indirect effect of job stress on job performance through job commitment and job satisfaction of employees of public accounting firms.